Structure–Function Relationship and Diagnostic Value of Macular Ganglion Cell Complex Measurement Using Fourier-Domain OCT in Glaucoma - Kim, Na Rae; Lee, Eun Suk; Seong, Gong Je; Kim, Ji Hyun; An, Hyong Gin; Kim, Chan Yun (Investigative ophthalmology & visual science, 2010)
To assess the relationship between visual function and macular ganglion cell complex (GCC) thickness measured by Fourier-domain optical coherence tomography (OCT) and to evaluate the diagnostic value of GCC thickness for detecting early, moderate, and severe glaucoma. Participants underwent reliable standard automated perimetry testing and OCT imaging with optic nerve head (ONH) mode and GCC mode within a single day. The relationship between structure and function was evaluated by comparing GCC thickness with mean deviation (MD) and visual field index (VFI), by regression analysis. The results were compared with those obtained for retinal nerve fiber layer (RNFL) thickness. The area under the receiver operating characteristic curve (AUC) was used to determine the relationship between disease severity and glaucomatous changes in RNFL and GCC parameters. One hundred three normal control subjects and 138 patients with glaucoma were included in the present study. Compared with linear models, second-order polynomial models better described the relationships between GCC thickness and MD (P<0.001), and between GCC thickness and VFI (P<0.001). A GCC pattern parameter, global loss volume (GLV), had the highest AUC for detecting early glaucoma. The AUC of mean GCC thickness for early glaucoma was higher than that of mean RNFL; however, the difference was not significant (P=0.330). A curvilinear function best described the relationship between VF sensitivity and GCC thickness. Macular GCC thickness and RNFL thickness showed similar diagnostic performance for detecting early, moderate, and severe glaucoma.